The transformative impact of information and communication technology on regional economies in Indonesia - Wardhana, Adhitya; Kharisma, Bayu; Fauzy, M. Zidan; Anggana, Adrian Kevianta (Optimum: Jurnal Ekonomi dan Pembangunan, 2025)
The development of information communication technology (ICT) has made it easier for people to carry out activities. People's dependence on ICT has become greater, which impacts increasing per capita income, business efficiency, and costs. The impact of ICT causes the flow of goods and services to be more efficient so that economic growth can be faster. This study aims to analyze the effect of ICT on economic development across all provinces in Indonesia over the period 2012–2022. The data used in this study from the Central Bureau of Statistics and the DJPK or the Ministry of Finance of Indonesia and used Generalized Least Squares (GLS) model approach. The results shows the Information and Communication Technology Development Index as a proxy for ICT, government spending, and investment significantly affected economic growth in all provinces. The labor variable does not significantly affect economic growth. The investment variable has the power prediction on economic growth. Implication of the study the government needs to build digital infrastructure and  government budget is more focused on digital literacy.